Estructura juridica de los precios públicos y su falta de regulacion. - Puertas Monteros, Santiago Israel (2011)
The present thesis of investigation contains a study about the definition elements classification and nature of de rates and public prices, determined besides their principal relation similarities and differences, at the end of calling attention about the necessity of contacting in our country with a judicial mark that may establish the quantity of these last, for their lack creates some legal disputes, in order to comply with the principle of legal certainty, for both the entity providing the service area of the counter display, and the rights and the consumer that requires the enforcement of its tights in respect of the amount of price and service quality, with this purpose in the work we analyze further the categories of taxes, its principles and classification, the origin of the tax protest and constitutional and legal framework on the rates in our country as well as an analysis of comparative law regarding rates and public prices.